2012
DOI: 10.1620/tjem.227.269
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Transarterial Chemoembolization Benefits Patients with High γ-Glutamyl Transferase Levels after Curative Hepatectomy for Hepatocellular Carcinoma: A Survival Stratification Analysis

Abstract: Hepatocellular carcinoma (HCC) is the most common liver tumor in Asian countries, and hepatectomy is currently regarded as the optimal curative treatment for HCC; however, the postoperative outcome remains unsatisfactory. Aiming at further clarification of prognostic factors after hepatectomy, we adopted a detailed stratification on survival periods. A total of 428 HCC patients undergoing curative hepatectomy were firstly divided into two groups using 2-year survival as cutoff point. Multivariate analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[1220] For the adjuvant TACE, the absence of tumor contributed to a complicated influence by changing the micro–environment of tumor, although the concentration of chemotherapy drugs were increased through the embolism. The hypoxia effect caused by TACE procedure, also led to the ischemia of tumor–free hepatocytes, stimulating the expression of vascular endothelial growth factor (VEGF) and activation of related signaling pathways, which induced the neoangiogenesis and formed tumor favorite micro–environment.…”
Section: Discussionmentioning
confidence: 99%
“…[1220] For the adjuvant TACE, the absence of tumor contributed to a complicated influence by changing the micro–environment of tumor, although the concentration of chemotherapy drugs were increased through the embolism. The hypoxia effect caused by TACE procedure, also led to the ischemia of tumor–free hepatocytes, stimulating the expression of vascular endothelial growth factor (VEGF) and activation of related signaling pathways, which induced the neoangiogenesis and formed tumor favorite micro–environment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, postoperative TACE can cause progressive liver atrophy or hepatic insufficiency and liver function impairment. [ 26 , 27 ] On this basis, we thought that postoperative TACE should not be abused in these patients. Although in the high-risk subgroups, patients received 2 or 3 postoperative TACE showed better DFS and OS compared to those received no or 1 TACE.…”
Section: Discussionmentioning
confidence: 99%
“…A mass of independent prognostic factors, such as serum γ-glutamyl transpeptidase and neutrophil-to-lymphocyte ratio, had been reported as of predicting values for the prognosis of PLC after hepatic resection. 8 , 9 Red blood cell (RBC) count is one of the erythrocyte parameters, and a very limited number of studies have reported that it can be used as a screening index or a treatment effect predictor of certain diseases. 10 , 11 One report has suggested the relation of elevated red cell distribution width with advanced liver fibrosis in nonalcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%